2021
DOI: 10.2147/ijgm.s320611
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lurasidone and Other Antipsychotics on Body Weight: Real-World, Retrospective, Comparative Study of 15,323 Adults with Schizophrenia

Abstract: Purpose The primary objectives were to describe weight changes following initiation of lurasidone versus other antipsychotics and estimate the risk of clinically relevant (≥7%) weight changes. Patients and Methods This retrospective, longitudinal comparative cohort study was based on electronic medical records (EMRs) of United States (US) adult patients with schizophrenia who were prescribed lurasidone or other antipsychotics as monotherapy between 1 April 2013 and 30 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…The underlying mechanism behind this is suggested to be due to changes to the gut microbiota which potentiate an obesogenic profile. This has led to the proposition that all antipsychotics are detrimental to metabolic functioning and the gut microbiota (Davey et al, 2013; Hao et al, 2023; Minichino et al, 2023; Munawar et al, 2021; Pochiero et al, 2021; Qian et al, 2023; Seeman, 2021). Lurasidone, another atypical second-generation antipsychotic, has received lesser investigation with its impact of body weight and metabolic function not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism behind this is suggested to be due to changes to the gut microbiota which potentiate an obesogenic profile. This has led to the proposition that all antipsychotics are detrimental to metabolic functioning and the gut microbiota (Davey et al, 2013; Hao et al, 2023; Minichino et al, 2023; Munawar et al, 2021; Pochiero et al, 2021; Qian et al, 2023; Seeman, 2021). Lurasidone, another atypical second-generation antipsychotic, has received lesser investigation with its impact of body weight and metabolic function not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both drugs possess comparable indications (schizophrenia and bipolar disorder) and comparable adverse drug event profile (including movement disturbances and sedation) (Meltzer et al, 2011). However, despite these similarities, lurasidone's impact on the gut microbiota remains unexplored and retrospective comparative studies such as one by Pochiero et al indicate a contrastive weight gain profile compared to most antipsychotics with lurasidone-induced weight gain and weight loss conclusions both being drawn (Pochiero et al, 2021). Thus, lurasidone remains prime for studies exploring its impact on the gut microbiota, serving as the motivation for this study.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study conducted on 15,323 adults suggest that lurasidone has a lower risk of clinically relevant weight gain and a higher chance of clinically relevant weight loss than other commonly used antipsychotics. 44 Two other real-world studies have also shown the higher adherence to treatment and the lower rate of hospital admissions associated with lurasidone treatment, compared with other antipsychotic treatments, 45,46 with an associated improvement in quality of life. 47 In addition, recent practical guidelines on the use of lurasidone for the treatment of adult patients with schizophrenia as well as the results from a meta-analysis have confirmed the role of lurasidone in both the acute and maintenance phases of treatment for schizophrenia in adults.…”
Section: Studymentioning
confidence: 96%
“…The results of a study conducted on 15,323 adults suggest that lurasidone has a lower risk of clinically relevant weight gain and a higher chance of clinically relevant weight loss than other commonly used antipsychotics. 44 Two other real-world studies have also shown the higher adherence to treatment and the lower rate of hospital admissions associated with lurasidone treatment, compared with other antipsychotic treatments, 45 , 46 with an associated improvement in quality of life. 47 …”
Section: Introductionmentioning
confidence: 95%
“…Based on its pharmacological profile, lurasidone is associated with fewer extra-pyramidal symptoms than conventional agents and effectively ameliorates various schizophrenic symptoms [ 5 , 7 ]. Lurasidone has a lower risk of weight gain or metabolic disturbances than other commonly used antipsychotics [ 8 , 9 ]. Based on the effect of concomitant food intake on the bioavailability of lurasidone [ 10 ], dosing instructions recommend the use of lurasidone with a meal of at least 350 kcal caloric value to optimize its relevant pharmacokinetic parameters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%